Role and mechanisms of a three-dimensional bioprinted microtissue model in promoting proliferation and invasion of growth-hormone-secreting pituitary adenoma cells. (6th February 2019) - Diao, Jinfu; Zhang, Chuanbao; Zhang, Dainan; Wang, Xiong; Zhang, Jing; Ma, Cheng; Deng, Kunxue; Jiang, Tao; Jia, Wang; Xu, Tao
Abstract: Growth-hormone-secreting pituitary adenoma (GHSPA) is a benign tumour with a high incidence and large economic burden, which greatly affects quality of life. The aetiological factors are yet to be clarified for GHSPA. Conventional two-dimensional (2D) monolayer culture of tumour cells cannot ideally reflect the growth status of tumours in the physiological environment, and insufficiencies of in vitro models have severely restricted the progress of cancer research. Three-dimensional (3D) bioprinting technology is being increasingly used in various fields of biology and medicine, which allows recapitulation of the in vivo growth environment of tumour cells. In this study, a GHSPA microtissue model was established using 3D bioprinting. Tumour cells in the 3D environment exhibited more active cell cycle progression, secretion, proliferation, invasion, and tumourigenesis compared with those in the 2D environment. Furthermore, the molecular mechanisms of the 3D-printed microtissue model were explored. We demonstrated that the 3D-printed microtissue provides an excellent in vitro model at the tissue level for oncological research and may facilitate in-depth studies on the aetiology, treatment, drug resistance, and long-term prognosis of GHSPA .